Design of Information and Communication Technology Teaching Materials Based on Contextual Teaching and Learning - Vidya Octavianti (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
Online learning during the COVID-19 pandemic has required the teaching and learning process to be conducted without face-to-face interaction. This condition has increased the demand for digital teaching materials that can effectively support students’ understanding, particularly in Information and Communication Technology (ICT) subjects. SMP Patra Mandiri 2 Palembang is equipped with a computer laboratory and internet facilities; however, these facilities have not been optimally utilized because teachers still rely on manual guidebooks for practical learning activities. This study aimed to design ICT teaching materials based on the Contextual Teaching and Learning (CTL) approach in the form of a website to support online learning. The system development employed the Extreme Programming (XP) method, which consists of the stages of planning, design, coding, and testing. The results of the study produced a CTL-based ICT teaching materials system that provides features for uploading learning materials, assignments, quizzes, question-and-answer interactions, and assessments that are accessible to both teachers and students. The system is expected to enhance the effectiveness of online learning and to promote active student engagement in understanding learning materials through a contextual approach.